Digital Animasi 2 Dimensi Dengan Metode Cell Shadding Dan Rigging Bone Studi Kasus : Legenda Gunung Tugel - Fendi Aji Purnomo; Eko Harry Pratisto; Agus Purnomo; Ahzan Saiful Huda; Ady Setyo Nugroho (IJAI (Indonesian Journal of Applied Informatics), 2017)
Mature Indonesian culture is now diminishing. Indonesian society, increasingly popular by the outside culture through the development of increasingly sophisticated technology. One is the story of a growing legend in their respective regions, so it becomes ironic as children today are uncertain of not caring about their own culture. One of the growing legend stories is "Gunung Tugel" which originated from Boyolali area, which tells about wisdom and culture.Media education currently popular by the public one of them is the animated film. The animated film "Legend of Mount Tugel" is built using the 2 Dimension method, which has a duration of 20 minutes, with the specification of .mp4 extension, 1280x720 video resolution, and frame rate of 24 fps. In making the film, use Moho Anime Studio software to create animations, then Adobe Illustrator, CorelDraw, and Photoshop, for modeling, and Adobe After Effect for video editing process.Based on a questionnaire assessment that has been conducted on 41 respondents, it can be seen that as much as 79% considered that the animated film "Legend of Gunung Tugel" is good value in the character design aspect of the character. As for other aspects, such as audio as much as 85% interesting. Aspects of visual effects, as much as 76% interesting, and environmental aspects of good value of 77%